2018
DOI: 10.1155/2018/4278782
|View full text |Cite
|
Sign up to set email alerts
|

Sinc-Windowing and Multiple Correlation Coefficients Improve SSVEP Recognition Based on Canonical Correlation Analysis

Abstract: Canonical Correlation Analysis (CCA) is an increasingly used approach in the field of Steady-State Visually Evoked Potential (SSVEP) recognition. The efficacy of the method has been widely proven, and several variations have been proposed. However, most CCA variations tend to complicate the method, usually requiring additional user training or increasing computational load. Taking simple procedures and low computational costs may be, however, a relevant aspect, especially in view of low-cost and high-portabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As explained in section 3.2, the first column of W b is used as spatial filter. However, Mondini et al [104] recently hypothesized that relevant information might be spread over more than one coefficient. For that reason, several studies opted to concatenate the projected responses of n filters w b1 , w , .…”
Section: Alternative Spatial Filtersmentioning
confidence: 99%
“…As explained in section 3.2, the first column of W b is used as spatial filter. However, Mondini et al [104] recently hypothesized that relevant information might be spread over more than one coefficient. For that reason, several studies opted to concatenate the projected responses of n filters w b1 , w , .…”
Section: Alternative Spatial Filtersmentioning
confidence: 99%
“…However, due to the noisiness of the EEG, information may be distributed over several coefficients 5 . Recently, Mondini et al 26 showed that considering multiple correlations can improve signal classification.…”
Section: Methodsmentioning
confidence: 99%
“…The authors tested several different decomposition designs: equally spaced, harmonic and overlapping sub-bands, and observed that the latter yielded the highest accuracy. Recently, Monidini et al 26 investigated the number of correlations coefficients considered for CCA classification and found a significant improvement in classification accuracy if more than one coefficients (as in the conventional approach) were considered.…”
mentioning
confidence: 99%
“…Typically, only the first canonical correlation and corresponding weight is used for classification and construction of filters [4, 5, 29]. Nonetheless, some recent studies yielded better performance when the additional canonical variable pairs with their associated correlations and weights where also utilized [30].…”
Section: Methodsmentioning
confidence: 99%